Clinical study on bronchial artery chemoembolization for unresectable non-small cell lung cancer - Zhang, Fenxiang; Liu, Yujin (Frontiers in Oncology, 2025)
ObjectiveTo investigate the efficacy and safety of bronchial artery chemoembolization (BACE) for the treatment of inoperable non-small cell lung cancer (NSCLC).MethodsA retrospective review was conducted of 112 patients with NSCLC who received BACE treatment and 120 patients who underwent systemic chemotherapy in our center over the past 10 years. The progression-free survival (PFS), overall survival (OS), objective response rate (ORR), quality of life, and adverse events were compared between the two groups.ResultsThe complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD) rates in the BACE group were 7.14%, 39.29%, 33.04%, and 20.54%, respectively, while those rates in the chemotherapy group were 7.5%, 20.83%, 55.0%, and 16.67%. The ORR in the BACE group was significantly higher than in the chemotherapy group (46.43% vs. 28.33%, P = 0.007). The median PFS was significantly longer in the BACE group (17 months vs. 11 months, P = 0.035) than that of chemotherapy group, as was the median OS (19.5 months vs. 13 months, P = 0.044). The BACE group also showed significantly better results in cough relief (57.0% vs. 41.7%, P = 0.028) and hemoptysis relief (70.3% vs. 47.1%, P = 0.001) compared to the chemotherapy group. The 1-year, 3-year, and 5-year survival rates for the BACE group were 68.0%, 29.1%, and 15.5%, respectively, compared to 49.5%, 15.9%, and 7.5% those of the chemotherapy group, with statistically significant differences (P < 0.05). The BACE group exhibited better tolerability and higher safety, with a lower incidence and severity of adverse events, particularly fatigue, nausea/vomiting, and myelosuppression, which showed statistically significant differences (P < 0.05).ConclusionBACE treatment for inoperable NSCLC offers better clinical outcomes compared to systemic chemotherapy and is safe and well-tolerated, with no severe adverse events. This approach warrants further prospective randomized controlled trials.